2002
DOI: 10.1038/nature00892
|View full text |Cite
|
Sign up to set email alerts
|

A neural correlate of response bias in monkey caudate nucleus

Abstract: Primates are equipped with neural circuits in the prefrontal cortex, the parietal cortex and the basal ganglia that predict the availability of reward during the performance of behavioural tasks. It is not known, however, how reward value is incorporated in the control of action. Here we identify neurons in the monkey caudate nucleus that create a spatially selective response bias depending on the expected gain. In behavioural tasks, the monkey had to make a visually guided eye movement in every trial, but was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
338
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(378 citation statements)
references
References 25 publications
37
338
2
1
Order By: Relevance
“…Several recent studies have characterized the influence of reward expectation on neural circuits involved in sensory-motor transformations [14,16 -20]. The study by Lauwereyns and colleagues [4] adds to that short list and provides novel insights into how the brain might use signals related to a spatially selective anticipation of reward to bias a simple oculomotor behavior. It will be interesting to see whether the same principles can be extended to include other factors and more complex behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have characterized the influence of reward expectation on neural circuits involved in sensory-motor transformations [14,16 -20]. The study by Lauwereyns and colleagues [4] adds to that short list and provides novel insights into how the brain might use signals related to a spatially selective anticipation of reward to bias a simple oculomotor behavior. It will be interesting to see whether the same principles can be extended to include other factors and more complex behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, despite a growing body of work identifying neural circuits that represent information related to reward in the context of sensory -motor tasks [3], how these kinds of signals might influence behavior is a mystery. A recent study by Lauwereyns and colleagues has begun to shed light on this difficult issue [4]. The results describe neural signals in a region of the basal ganglia called the caudate nucleus that appear to relate anticipation of an uncertain reward with the preparation for a goal-directed eye movement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Nakamura et al, 1992;Braesicke et al, 2005). Motivational influences on saccadic reaction time are reproduced using incentive value signals broadcast by orbitofrontal cortex (Lauwereyns et al, 2002;Roesch and Olson, 2003). 3a: Simulated blood pressure output (right) compared with recorded blood pressure (left) during CS Task performance [Reprinted with permission from Nakamura et al (1992)].…”
Section: Neurobiological Basis Of the Modelmentioning
confidence: 99%
“…Saccadic response time (SRT) is correlated with the time it takes a visually-selective FEF cell to respond to a target in its receptive field during visual discrimination (Sato et al, 2001). Numerous studies have demonstrated that target salience is one of the attributes that can speed the discrimination of targets from distractors (Lauwereyns et al, 2002;Roesch and Olson, 2004). Incentive motivation also impacts SRT, but the timing of instrumental saccades involves dorsal striatal mechanisms (Corbit et al, 2001;Brown et al, 2004).…”
Section: Saccade Latencymentioning
confidence: 99%